Intersectoral costs of sexually transmitted infections (STIs) and HIV: a systematic review of cost-of-illness (COI) studies - Lena Schnitzler; Louise J. Jackson; Aggie T. G. Paulus; Tracy E. Roberts; Silvia M. A. A. Evers (BMC, 2021)
Abstract Background Sexually transmitted infections (STIs) and HIV can generate costs both within and outside the health sector (i.e. intersectoral costs). This systematic review aims (i) to explore the intersectoral costs associated with STIs and HIV considered in cost-of-illness (COI) studies, (ii) to categorise and analyse these costs according to cost sectors, and (iii) to illustrate the impact of intersectoral costs on the total cost burden. Methods Medline (PubMed), EMBASE (Ovid), Web of Science, CINAHL, PsycINFO, EconLit and NHS EED were searched between 2009 and 2019. Key search terms included terms for cost-of-illness, cost analysis and all terms for STIs including specific infections. Studies were included that assessed intersectoral costs. A standardised data extraction form was adopted. A cost component table was established based on pre-defined sector-specific classification schemes. Cost results for intersectoral costs were recorded. The quality of studies was assessed using a modified version of the CHEC-list. Results 75 COI studies were considered for title/abstract screening. Only six studies were available in full-text and eligible for data extraction and narrative synthesis. Intersectoral costs were captured in the following sectors: Patient & family, Informal care and Productivity (Paid Labour). Patient & family costs were addressed in four studies, including patient out-of-pocket payments/co-payments and travel costs. Informal care costs including unpaid (home) care support by family/friends and other caregiver costs were considered in three studies. All six studies estimated productivity costs for paid labour including costs in terms of absenteeism, disability, cease-to-work, presenteeism and premature death. Intersectoral costs largely contributed to the total economic cost burden of STIs and HIV. The quality assessment revealed methodological differences. Conclusions It is evident that intersectoral costs associated with STIs and HIV are substantial. If relevant intersectoral costs are not included in cost analyses the total cost burden of STIs and HIV to society is severely underestimated. Therefore, intersectoral costs need to be addressed in order to ensure the total economic burden of STIs and HIV on society is assessed, and communicated to policy/decision-makers.